The effect of interleukin-15 on the expression of killer-cell immunoglobulin-like receptors on peripheral natural killer cells in human - Toshiaki Kogure; Naoki Mantani; Hirozo Goto; Yutaka Shimada; Jun'ichi Tamura; Katsutoshi Terasawa (Hindawi Limited, 2002)
Interleukin (IL)-15 has emerged as a key regulator of both natural killer (NK) cell differentiation and activation. The aim of the present study was to investigate the expansion of the population of cells expressing killer-cell immunoglobulin-like receptors (CD158a and CD158b) in human peripheral lymphocytes by treatment with IL-15. One million peripheral lymphocytes were cultured in RPMI1640 medium alone or in medium containing IL-2 at 100 U/ml or IL-15 at 0.1, 1.0, or 10.0 ng/ml for 48 h. After each incubation, we assessed the natural killing activity and the population of CD16+CD158a+/b+ cells and CD8+CD158a+/b+ cells. IL-15 increased the NK activity and expanded the populations of CD16+CD158a+/b+ cells and CD8+CD158a+/b+ cells. These actions were dose dependent, and the effects of IL-15 at 1.0 ng/ml were close to those of IL-2 at 100 U/ml. These findings suggest that IL-15 induces the effector functions of resting NK cells throughout the body, and thereby plays a critical role in the activation of tissue-associated immune responses.